STRATEGIC ADAPTABILITY FOR MARKET LEADERSHIP IN INDONESIA’S BABY CARE INDUSTRY USING SCENARIO PLANNING - Dinda Rahma Sesha; Utomo Sarjono Putro (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The Indonesian baby care industry faces uncertainty driven by economic volatility, rapid digital transformation, changing consumer preferences, demand for product safety, and intensifying competition. These conditions challenge companies to maintain long-term market leadership using strategic planning approaches. This study aims to develop strategic adaptability for sustaining market leadership in Indonesia’s baby care industry through a scenario planning approach. This research conducted a qualitative method using semi-structured interviews with internal and external industry experts. Interview findings were formulated into driving forces, followed by prioritization assessment to identify the two major critical uncertainties shaping the future industry environment. Then, the four plausible future scenarios were developed, namely The Battle Arena, The Golden Age, The Dark Times and The Old Guard, along with early warning signals to anticipate changes in macroeconomic and industry conditions. The findings indicate that strategic adaptability is essential for sustaining market leadership under uncertain market condition. The study further integrated scenario planning with an evaluation of current strategy to identify strategic gaps under future scenario. A TOWS matrix was subsequently formulated. It resulted in several strategic recommendation pillars with different adaptive adjustments across scenarios, followed by implementation roadmap for the next five years.